Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1103/physrevb.36.4479
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative "local-interference" model for1fnoise in metal films

Abstract: Electron scattering calculations by Martin are used to predict the magnitude of resistivity fluctuations in metal films arising from the fluctuating interference of electrons in the local environment of a moving defect. A "local-interference" model based on these calculations accounts for the 1/f-noise magnitude observed in irradiated Cu films and in room-temperature metal films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 15 publications
3
58
0
Order By: Relevance
“…These processes takes place on a length scale typical of the spacing between neighboring defects l e hence, the induced noise is called ''local interference'' noise. 48 The local interference processes do not vary with small magnetic fields. A crude way of accounting for the mixture of local interference and long-range interference ͑i.e., UCF͒ noise in our samples is to add an extra fitting parameter called the ''fraction UCF'', or f UCF .…”
Section: /F Noise and Universal Conductance Fluctuationsmentioning
confidence: 99%
“…These processes takes place on a length scale typical of the spacing between neighboring defects l e hence, the induced noise is called ''local interference'' noise. 48 The local interference processes do not vary with small magnetic fields. A crude way of accounting for the mixture of local interference and long-range interference ͑i.e., UCF͒ noise in our samples is to add an extra fitting parameter called the ''fraction UCF'', or f UCF .…”
Section: /F Noise and Universal Conductance Fluctuationsmentioning
confidence: 99%
“…In disordered metallic systems these fluctuations, often known as 1/f -noise, are extremely sensitive to slow relaxation of defects (dislocations, cluster of point defects etc). Random movement of the scatterers, even at a scale ∼ Fermi wavelength (λ F < ∼ 1 nm), change the interference pattern of coherently back-scattered electrons, reflecting in the time-dependent fluctuations in the resistivity [15]. In magnetic systems, the DWs themselves can act as scatterers of spinpolarized conduction electrons, and modify the R of the nanowires.…”
mentioning
confidence: 99%
“…To account for field-independent local interference noise [31,32] at higher temperatures, a second fitting parameter, z, the fraction of noise that is due to UCF, was introduced into the fitting function, f (B) = (1 − z) + zν(B). We found that z was indistinguishable from 1 for all temperatures measured except for 20 K in the 2d samples, when z ≈ 0.68.…”
mentioning
confidence: 99%